The Titanic Series: Reflections on Cambridge University Press’s Edition of the Literary Works of Joseph Conrad - Watts, Cedric (Studia Anglica Posnaniensia, 2019)
In this essay, therefore, I use a sequence of comparisons to demonstrate the presence of a pattern of flaws. The sequences are taken from Notes on Life and Letters, ’Twixt Land and Sea / Tales, Last Essays, Lord Jim, and The Nigger of the “Narcissus”. I compare extracts from the Cambridge texts with extracts taken from other editions.